2004
DOI: 10.1103/physrevc.70.054601
|View full text |Cite
|
Sign up to set email alerts
|

Higher order effects in theO16(d,p)O17and

Abstract: Full coupled channels calculations were performed for the 16 O͑1/2 + , 0.87͒ was observed. This polarization effect had to be taken into account in order to obtain realistic spectroscopic factors from these reactions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…However, it has been shown that s-wave neutron capture, even at rather low energies, is not peripheral [11,12] and so it is necessary to use a potential model to calculate the wave function of the incoming neutron in this case. This indirect approach, based on the potential model, has been recently applied in the analysis of the 16 [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that s-wave neutron capture, even at rather low energies, is not peripheral [11,12] and so it is necessary to use a potential model to calculate the wave function of the incoming neutron in this case. This indirect approach, based on the potential model, has been recently applied in the analysis of the 16 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The spectroscopic factor describes the overlap between the initial and final states and yields the information on the occupancy of a given single-particle orbit, which plays an important role in a variety of topics on nuclear reaction and nuclear astrophysics. Single-nucleon transfer reactions such as (d, p) and (d, n) have been used extensively to extract the spectroscopic information of the single-nucleon orbits in nuclei located at or near the stability line [1][2][3]. The spectroscopic study of exotic nuclei becomes feasible since the production of radioactive ion beams [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of the bound-state real potentials p+ 10 Be, p+ 11 B and d+p was fixed to r o = 1.25 fm and a = 0.65 fm and the depths were adjusted to reproduce the binding energy of the transfered proton. For the deuteron p+n bound state, two different binding potentials were used: the Reid Soft Core (RSC) tensor potential and a Gaussian form V pn = −v 0 exp(−r 2 /a 2 ) with a = 1.484 fm and v 0 = 72.15 MeV [18] but no significant difference between these two was observed. The spectro- Table II.…”
Section: Dwba Analysismentioning
confidence: 99%